2017
DOI: 10.1002/ejic.201601374
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Uranyl Ion with Sulfonates: One‐ to Three‐Dimensional Assemblies with 1,5‐ and 2,7‐Naphthalenedisulfonates

Abstract: International audienceUranyl nitrate was reacted with the sodium salt of either 1,5- or 2,7-naphthalenedisulfonate (1,5-ndsNa2 and 2,7-ndsNa2, respectively) under (solvo)-hydrothermal conditions, in the presence of additional coligands and/or metal cations, to give six new complexes which were characterized by their crystal structure determinations. [UO2(1,5-nds)(H2O)] (1) crystallizes as a three-dimensional (3D) framework, with both sulfonate groups coordinated in the O,Oʹ-bridging mode. In the presence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Sodium naphthalene-1,5-disulfonate (see Figure and Table ) is the sodium salt of 1,5-naphthalenedisulfonate, which crystallizes in the space group P 2 1 /c and adopts three-dimensional frameworks constructed by inorganic–organic layers, with the metal–sulfonate inorganic portions pillared by the naphthalene rings. , The weaker ligation of sulfonate networks generally show more promise than phosphonates for dynamic materials where structural flexibility is desired. Moreover, it does make (monocrystal to monocrystal) solid state kinetics possible, and it has attracted more and more attention in coordination polymer chemistry. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium naphthalene-1,5-disulfonate (see Figure and Table ) is the sodium salt of 1,5-naphthalenedisulfonate, which crystallizes in the space group P 2 1 /c and adopts three-dimensional frameworks constructed by inorganic–organic layers, with the metal–sulfonate inorganic portions pillared by the naphthalene rings. , The weaker ligation of sulfonate networks generally show more promise than phosphonates for dynamic materials where structural flexibility is desired. Moreover, it does make (monocrystal to monocrystal) solid state kinetics possible, and it has attracted more and more attention in coordination polymer chemistry. , …”
Section: Introductionmentioning
confidence: 99%
“…The relatively weak coordination of sulfonate anions facilitates formation of crystalline products for sodium naphthalene-1,5-disulfonate . Crystallization is an important process for improving the quality of crystalline products, such as purity, polymorph, morphology, and crystal size distribution, and in the optimization of crystallization processes, the solubility data of sodium naphthalene-1,5-disulfonate in the commonly used neat and binary solvent systems are essential.…”
Section: Introductionmentioning
confidence: 99%
“…36 When compared to the use of carboxylate ligands, disulfonate linkers have rarely been investigated, likely due to their weaker coordination strength which has been thought to hinder their ability to act as building blocks in the construction of coordination polymers. [37][38][39][40] However, because disulfonate groups have more oxygen atoms that can potentially bind to metal ions and given these oxygen atoms are nonplanar, this means that disulfonate linkers have increased versatility in terms of coordination modes, which in turn allows for the construction of coordination polymers with more diverse architectures. [41][42][43][44] Furthermore, sulfonate-based coordination polymers usually show good water-stability over a wide pH and temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…37 Previous studies have also demonstrated that sulfonate ligands are capable to function as supramolecular linker to construct Q[n]-based supramolecular assemblies. 40,44,45 Herein, we have attempted to introduce disulfonate linkers via the use of naphthalene disulfonic acids (H 2 NDA), including 1,5-H 2 NDA, 2,6-H 2 NDA and 2,7-H 2 NDA derivatives (Scheme 1) into Q[n]-M 2+ (M = Ca, Sr and Ba) type systems. On reaction of H 2 NDA with Q [6] and alkalineearth metal ions, we obtained a series of Q [6]-based coordination complexes in which the 4 carbonyl groups of Q [6] were directly bound to the metal ions, namely [Ca(H 2 O) 4 (Q [6]) 0.5 (1,…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in uranyl and mixed uranyl-lanthanide complexes of psulfonatocalix [4]arene, chelation of a sulfonate group is observed but only on a uranyl centre, 9 being perhaps an index of the greater Lewis acidity of U VI compared to that of Ln III . It is true, however, that this is a rare case of κ 2 O,O' sulfonate chelation, with κ 1 O or µ2-κ 1 O;κ 1 O' binding modes being of far more frequent occurrence in the relatively limited number of known uranyl sulfonate structures, [10][11][12][13][14][15][16][17][18][19][20][21][22][23] although not all of these involve ligands in which sulfonate groups are the only functionality. In extension of our studies of the influence of large complex cations upon the crystal structure of anionic uranyl ion complexes and coordination frameworks, [24][25][26][27][28][29] a field undergoing considerable expansion, [30][31][32][33][34] therefore, we have sought to define the influence of such cations on the structure of complexes formed with a variety of ligands incorporating sulfonate donors, a study which has confirmed the rarity of sulfonate chelation to uranyl ion but which has also provided indication of the energy of sulfonate hydrogen bonding interactions, widely studied in systems not containing metal ions, 1,35,36 which compete with metal ion coordination.…”
Section: Introductionmentioning
confidence: 99%